TEOLOGI SEBAGAI PILAR UTAMA PENGEMBANGAN PENDIDIKAN KRISTEN DI LINGKUNGAN GEREJA - Parebong, Wawan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT The church is a community of believers called to proclaim the truth based on the teachings of Scripture, one of which is through the implementation of Christian Religious Education (CRE). This responsibility is ongoing, as the spiritual formation of the congregation must be continuously nurtured. In facing modernization, changes in lifestyle among church members, and the rise of teachings that deviate from God’s Word, the church needs to develop CRE that is grounded in theology. The content and direction of CRE stem from theological reflection that reveals God's will. Therefore, theology serves as a vital foundation in designing biblical CRE instruction aimed at shaping spiritually mature believers who can live out their faith in daily life. This article utilizes a qualitative descriptive approach, based on literature study. The data were obtained through the exploration and analysis of various sources such as books, scholarly journals, and relevant references in order to explore theological understanding as the foundation for the development of Christian Religious Education (CRE). The findings underscore the importance of recognizing PAK as a central mission of the church that must be nurtured and expanded. As a theological endeavor, PAK must be developed with theology as its guiding principle—ensuring that Christian education within the church remains doctrinally sound and spiritually transformative. ABSTRAK Gereja adalah komunitas orang percaya yang dipanggil untuk menyampaikan kebenaran berdasarkan ajaran Kitab Suci, salah satunya melalui penyelenggaraan Pendidikan Agama Kristen (PAK). Tanggung jawab ini bersifat berkelanjutan karena pembinaan iman jemaat harus terus dilakukan. Dalam menghadapi modernisasi dan perubahan gaya hidup jemaat, serta tantangan ajaran yang menyimpang dari firman Tuhan, gereja perlu mengembangkan PAK yang berlandaskan teologi. Sebab, isi dan arah PAK bersumber dari refleksi teologis yang menjelaskan kehendak Allah. Dengan demikian, teologi menjadi dasar penting dalam merancang pengajaran PAK yang alkitabiah untuk membentuk jemaat yang matang secara rohani dan mampu menghidupi imannya dalam keseharian. Artikel ini disusun dengan pendekatan deskriptif kualitatif melalui studi literatur. Data diperoleh melalui penelusuran dan analisis terhadap berbagai sumber seperti buku, jurnal ilmiah, dan referensi relevan guna menggali pemahaman teologis sebagai dasar pengembangan Pendidikan Agama Kristen (PAK). Hasil dari kajian ini menegaskan bahwa PAK merupakan bagian integral dari misi gereja yang tidak boleh diabaikan. Sebagai wujud karya teologis, PAK harus dikembangkan secara konsisten dengan landasan teologi yang kokoh, agar gereja dapat menumbuhkan jemaat yang kuat dalam iman dan aktif dalam pelayanan.